Sequelae of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection among Kidney Transplant Recipients: A Large Single-Center Experience - Zona, Emily E.; Gibes, Mina L.; Jain, Asha S.; Danobeitia, Juan S.; Garonzik-Wang, Jacqueline; Smith, Jeannina A.; Mandelbrot, Didier A.; Parajuli, Sandesh (Critical Care Research and Practice, 2024)
Background. Kidney transplant recipients (KTRs) are a vulnerable immunocompromised population at risk of severe COVID-19 disease and mortality after SARS-CoV-2 infection. We sought to characterize the post-infection sequelae in KTRs at our center. Methods. We studied all adult KTRs (with a functioning allograft) who had their first episode of SARS-CoV-2 infection between 04/2020 and 04/2022. Outcomes of interest included risk factors for hospitalization, all-cause mortality, COVID-19-related mortality, and allograft failure. Results. Of 979 KTRs with SARS-CoV-2 infection, 381 (39%) were hospitalized. In the multivariate analysis, risk factors for hospitalization included advanced age/year (HR: 1.03, 95% CI: 1.02–1.04), male sex (HR: 1.29, 95% CI: 1.04–1.60), non-white race (HR: 1.48, 95% CI: 1.17–1.88), and diabetes as a cause of ESKD (HR: 1.77, 95% CI: 1.41–2.21). SARS-CoV-2 Vaccination was associated with decreased risk of hospitalization (HR: 0.73, 95% CI: 0.59–0.90), all-cause mortality (HR: 0.52, 95% CI: 0.37–0.74), and COVID-19-related mortality (HR: 0.47, 95% CI: 0.31–0.71) in the univariate and multivariate analyses. Risk factors for both all-cause and COVID-19-related mortality in the multivariate analyses included advanced age, hospitalization, and respiratory symptoms for hospital admission. Furthermore, additional risk factors for all-cause mortality in the multivariate analysis included being a non-white recipient and diabetes as a cause of ESKD, with being a recipient of a living donor as protective. Conclusions. Hospitalization due to COVID-19-associated symptoms is associated with increased mortality. Vaccination is a protective factor against hospitalization and mortality.